2024
DOI: 10.20944/preprints202401.1033.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water Supply Network Renewal Strategic Planning Utilizing the VIKOR Method

Goran Orasanin,
Stojan Simic,
Aleksandar Kosarac
et al.

Abstract: Water networks are critical infrastructure components, ensuring the continuous supply of high-quality drinking water to consumers. To secure such water supply, regular maintenance, including the replacement of deteriorating pipelines, is essential. In this study, a methodology has been developed for determining optimal pipeline replacement solutions in water supply systems at water utilities with limited data availability. Hydraulic analysis has been conducted on the segment of 25 km of the water supply networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, an urgency level rating was used in this study to prioritize the rehabilitation of the selected pipe network. Orasanin et al [31] determined the weights of the criteria for renewal of water supply networks using AHP. Altogether, 13 criteria were compared in this study, and the results revealed that water quality, investment value, frequency of failures, and pipe flow velocity possessed higher weights compared to other criteria such as pipe age, length, diameter, number of connections, soil condition, population density, pipe pressure, and hydraulic condition of the pipe.…”
Section: Figure 2 Structure Of the Ahpmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an urgency level rating was used in this study to prioritize the rehabilitation of the selected pipe network. Orasanin et al [31] determined the weights of the criteria for renewal of water supply networks using AHP. Altogether, 13 criteria were compared in this study, and the results revealed that water quality, investment value, frequency of failures, and pipe flow velocity possessed higher weights compared to other criteria such as pipe age, length, diameter, number of connections, soil condition, population density, pipe pressure, and hydraulic condition of the pipe.…”
Section: Figure 2 Structure Of the Ahpmentioning
confidence: 99%
“…Researchers [20][21][22][23][24][25][26][27][28][29][30] have used AHP for multi-criteria decision-making related to various aspects of road asset maintenance, including prioritizing maintenance options, identifying high-priority regions, identifying critical road asset elements, and comparing maintenance options. Similarly, AHP has been used to make maintenance-related decisions about water pipe assets, including identification of failure modes, prioritizing high-risk network segments, and identifying critical criteria for rehabilitation and high performance in the network [31][32][33][34][35].…”
Section: Research Significancementioning
confidence: 99%